Rebating antitrust fines to encourage private damages actions - Winand Emons; Severin Lenhard (University of Bern, Department of Economics, 2020)
To encourage private actions for damages in antitrust cases some jurisdictions subtract a fraction of the redress from the fine. We analyze the effectiveness of this policy. Such a rebate does not encourage settlement negotiations that would otherwise not occur. If, however, the parties settle without the rebate, the introduction of the reduction increases the settlement amount, yet at the price of reduced deterrence for those wrongdoers who are actually fined. Under a leniency program the rebate has no effect on the leniency applicant: she doesn't pay a fine that can be reduced. The overall effect of a fine reduction on deterrence is, therefore, negative.
Keywords: D43; K21; K42; L40; 330; antitrust; damages; deterrence; leniency